PERAN SERTA LEMBAGA PENDIDIKAN TINGGI DI KOTA SEMARANG DALAM MENDORONG PERTUMBUHAN PERBANKAN SYARI’AH DI KOTA SEMARANG - Suwanto Suwanto (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
The purpose of this research is intended to determine the role of the IAIN Walisongo Semarang in encouraging the growth of sharia banking in Semarang. A descriptive qualitative method is applied in order to obtain data in this study through collecting and analyzing the related literature to this research. Moreover observation, interviews and secondary data on the development of Islamic banking from sharia banking statistic Indonesian Banking are caried out. The finding shows that the IAIN Walisongo Semarang has a role in encouraging the growth of sharia banking in Semarang through the development discourse and discipline of Islamic economics to open a graduate studies program of applied science of Islamic banking, the establishment of Islamic financial institutions BMT Walisongo, cases and the concept of derivation Development Sharia Banking, Products and Services, Socialization, and Human Resource Competencies, Roles in providing competence human resources on Islamic banking, Development and Assistance to financing customers, dissemination of Islamic banking in the community, cooperation with agency of Sharia Financing, involvement of State Polytechnic of Semarang in Islamic banking in financing, and Encouraging society become customer of Islamic Banking. Finally the higher education institutions in Indonesia have an opportunity to meet the needs of Islamic banking industry through the activities of Tri Darma Perguruan Tinggi, especially to help the business sectors to alleviate the problems derivation and translation of national rules of Islamic Banking, products and services, socialization, and human resource competencies.